2018
DOI: 10.1103/physrevb.98.214435
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-spring behavior below the exchange length in hard-soft bilayers in multidomain configurations

Abstract: Exchange-coupled hard-soft biphase magnets are technologically relevant systems in that they enable tailoring the magnetization reversal process. Here, exchange-spring behavior is observed in CoFe 2 O 4 /FeCo bilayers for soft thicknesses as thin as 2 nm, at least four times below the exchange length of the system. This result is in contrast with the accepted theory for spring magnets that states that the exchange length defines the critical thickness below which both magnetic phases should be rigidly coupled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…(ii) The alloy also grows well beyond typical SSD values, and formation of domains in the soft phase eases spontaneous demagnetization of the hard when both phases are coupled. 31 Magnetization at low temperature (LT). Magnetization versus applied field measured at 10 K is shown in Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) The alloy also grows well beyond typical SSD values, and formation of domains in the soft phase eases spontaneous demagnetization of the hard when both phases are coupled. 31 Magnetization at low temperature (LT). Magnetization versus applied field measured at 10 K is shown in Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…For the above reasons, numerous studies on the CoFe 2 O 4 (hard)/Co-Fe (soft) composite are found in the literature, including composites prepared as powders, 29 dense pellets, 30 or thin films. 31 Some works have set the main focus on the preparation process (in situ studies), 28,32 while others have taken care of an in-depth structural characterization of the produced composites using spectroscopic techniques such as Raman 33 or Mössbauer spectroscopy. 34,35 Others have put great efforts on studying the inter-particle coupling from different perspectives, both using transmission electron microscopy (TEM), and measuring dm curves (Henkel plots).…”
Section: Introductionmentioning
confidence: 99%
“…The squareness ratio (M r /M s ) values corresponding to Fe5, Sr5, and FeSr5 were 1.34, 0.18, and 0.32, respectively. This parameter value represents whether the domain structure of materials has single-domain structure (>0.5) or multi-domain structure (<0.5) [74,75]. These results indicate that Fe favors single-domain formation and Sr favors the formation of multidomain structures.…”
Section: Magnetic Characterizationmentioning
confidence: 99%
“…This means that under the present magnetic configuration (antiparallel spin interfacial exchange) the core-shell system will have an ES-like behavior. This kind of magnetic exchange occurs in systems composed of hard and soft magnetic materials with comparable or small exchange length [28,29]. Therefore, we can assume that the finite-size effect (in this case NP of 2 and 4 nm) will have a strong influence on the appearance of the ES phenomenon.…”
Section: Hysteresis For Bi-magnetic Core-shell Np Varying the Interfacial Exchange Constantmentioning
confidence: 99%